Coupled heat transfer performance of a high temperature cup shaped porous absorber. (15th February 2016) - Meng, Xian-long; Xia, Xin-lin; Zhang, Shun-de; Sellami, Nazmi; Mallick, Tapas
Highlights: A newly designed VSR using cup-shaped Al2 O3 porous absorber is proposed. The absorber ensures lower heat loss and more uniform temperature distribution. The inner radiative exchange inside the VSR has been solved and discussed. The heat transfer performance has been compared at different window reflectivities, porosities and mass flow rates. The experimental verification is adopted and discussed. Abstract: In this article, a newly designed volumetric solar receiver (VSR) using cup-shaped Al2 O3 porous absorber is studied through numerical simulations and experimental verification. The absorber achieves several advantages including lower heat loss and higher uniformity of heat flux. The ray tracing method is adopted to obtain the external radiation source. The inner radiative exchange within the cavity is solved with the aid of User Defined Function (UDF). The heat transfer performance has been compared based on different parameters including window reflectivity, porosity and mass flow rate. The theoretical advantages of using cup-shaped Al2 O3 absorber are presented. The experimental verification is adopted based on sixteen-dish concentrator (SDC) platform.